2023
DOI: 10.3389/fimmu.2023.1073779
|View full text |Cite
|
Sign up to set email alerts
|

Advances in preventive vaccine development against HTLV-1 infection: A systematic review of the last 35 years

Abstract: IntroductionThe Human T-lymphotropic virus type 1 (HTLV-1) was the first described human retrovirus. It is currently estimated that around 5 to 10 million people worldwide are infected with this virus. Despite its high prevalence, there is still no preventive vaccine against the HTLV-1 infection. It is known that vaccine development and large-scale immunization play an important role in global public health. To understand the advances in this field we performed a systematic review regarding the current progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
(181 reference statements)
0
7
0
2
Order By: Relevance
“…Previous reviews are also available in the literature regarding developing an efficacious HTLV-1 vaccine [ 83 86 ]. The most recent study by Santana et al systematically reviewed the last 35 years efforts for developing HTLV-1 vaccine [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews are also available in the literature regarding developing an efficacious HTLV-1 vaccine [ 83 86 ]. The most recent study by Santana et al systematically reviewed the last 35 years efforts for developing HTLV-1 vaccine [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews are also available in the literature regarding developing an efficacious HTLV-1 vaccine [ 83 86 ]. The most recent study by Santana et al systematically reviewed the last 35 years efforts for developing HTLV-1 vaccine [ 83 ]. In their study, 25 articles were included, out of which 19 were peptide based, and 6 were viral vector-based vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…К настоящему времени предложено несколько профилактических мер, а именно: дородовой скрининг и обследование доноров крови и органов. Однако споры об экономической эффективности этих мер не утихают, что связано с географической гетерогенностью эндемичных по HTLV-1-инфекции территорий [79,80].…”
Section: зак лючениеunclassified
“…Разработка эффективной вакцины позволит ограничить или даже предотвратить передачу HTLV-1, а также снизить вирусную нагрузку у инфицированных пациентов и тем самым вероятность развития HTLV-1-ассоциированных заболеваний. На сегодня известно несколько типов HTLV-1-вакцин, находящихся на разных этапах испытаний: пептидно-белковые, инкапсулированные и содержащие адъювант; полиэпитопные; на основе ДНК, дендритных клеток, рекомбинантного вируса осповакцины и другие [79,80].…”
Section: согласноunclassified
“…Based on the knowledge advances in the HTLV-host interaction and in the biotechnology recent systematic reviews and reports showed a plethora of approaches for HTLV-1 vaccine candidates: viral like particles vectors and viral vectors (Vaccinia virus, Adenovirus and Sendai virus), dendritic cell and peptide-based vaccines, recombinant single proteins or multiepitope proteins expressed in different systems including molecules encapsulated using nanotechnology [ 9 13 ]. Of great interest 15 peptide stretches (from Gag and Gag-Pro-Pol polyproteins, Tax-1 and gp62) were presented from an epitope platform for HTLV-1 vaccine development of uniquely viral non-human pentapeptides to avoid cross-reaction, generating safe immunization based on peptides and mRNA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%